Комп'ютерно-лінгвістичні методи та засоби виявлення споживацького досвіду на веб-форумах - Тимовчак-Максимець, Оксана Юріївна (Національний університет "Львівська політехніка", 2013)
У дисертаційній роботі розв’язано важливу наукову задачу розроблення комп’ютерно-лінгвістичних методів та засобів виявлення споживацького досвіду в інформаційному наповненні веб-форумів, які б дали змогу налагодити процес виявлення споживацького досвіду в масивах слабоструктурованої інформації. Для розв’язання цієї задачі запропоновано означення поняття споживацького досвіду, побудовано його модель в інформаційному наповненні веб-форумів. Розроблено методи виявлення релевантних веб-форумів та глибинного пошуку дискусій на основі побудованих моделей параметризованих запитів до пошукових систем, метод декомпозиції інформаційного наповнення веб-форуму за комунікативною структурою на основі побудованої моделі, метод відсіювання текстів з високим рівнем заангажованості на основі маркерів мотивації автора, метод виявлення споживацького досвіду на основі маркерів. У прикладному аспекті розроблено програмно-алгоритмічний комплекс виявлення споживацького досвіду, а також структуру консолідованого інформаційного ресурсу споживацького досвіду та структури спеціалізованих словників, які дають змогу автоматизовано формувати конструкції для виявлення споживацького досвіду, використовуючи апарат регулярних виразів. В диссертационной работе решена важная научная задача разработки компьютерно-лингвистических методов и средств обнаружения потребительского опыта в информационном наполнении веб-форумов, которые позволили наладить процесс выявления потребительского опыта в массивах слабоструктурированной информации. Для решения этой задачи предложено определение понятия потребительского опыта, построена его модель в информационном наполнении веб-форумов. Разработаны методы выявления релевантных веб-форумов и глубинного поиска дискуссий на основе построенных моделей параметризованных запросов к поисковым системам, метод декомпозиции информационного наполнения веб-форума по коммуникативной структуре на основе построенной модели, метод отсеивания текстов с высоким уровнем заангажированности на основе маркеров мотивации автора, метод выявления потребительского опыта на основе маркеров. В прикладном аспекте, разработан программно-алгоритмический комплекс для выявления потребительского опыта. Разработана структура консолидированного информационного ресурса потребительского опыта и структуры специализированных словарей, позволяющих автоматизировано формировать конструкции для выявления потребительского опыта, для формирования которых был использован аппарат регулярных выражений. In the thesis an important scientific task of developing computer and linguistic methods and means for identifying consumer experience in Web forum content was resolved. The definition of consumer experience was suggested and its model within Web forum content was built. Methods for identifying relevant Web forums and threads on the basis of parameterized query templates as well as a method for decomposing Web forum content by its communication structure based on the developed model were suggested. Software and algorithmic complex for detecting consumer experience based on a specialized vocabulary was developed. In the first chapter an analysis of current trends in forming and accumulating subjective information is carried out. The notion “consumer experience” is defined, characteristic features and components as well as reasons for increased demand for consumer experience are analysed. Classification of Web systems accumulating subjective information is developed. The influence of social and communicative properties of Web forums on consumer experience accumulation is analysed. In the second chapter a model of communicative structure of Web forum content which allows parsing and processing content, which was created as a result of the communicative process among Web forum users, was built. Method for detecting and screening biased texts, which consists in calculating the level of bias on the basis of weighted author motivation markers, was suggested. Model of consumer experience in Web forum content on the bases of generalized model of consumer experience was built. In the third chapter the process of identifying consumer experience on the Web forums is analysed in detail. Methods for identifying relevant Web forums and Web forum treads based on parameterized query templates and algorithms of forming parameterized queries to global search engines were developed. In the chapter algorithms of decomposing content of Web forums were developed. An algorithm of decomposing content by its communication structure and an algorithm of identifying relevant atomic situations were developed. A method of identifying consumer experience based on classification of consumer experience markers and models of formal consumer experience utterances were suggested. In the fourth chapter software and algorithmic complex for detecting consumer experience in Web forum content was developed. A specialized vocabulary for identifying consumer experience which consists of an object aspects vocabulary and a vocabulary of consumer experience expression patterns was built. A consolidated information resource of consumer experience concerning educational services of Lviv Polytechnic National University was formed. Efficiency of the developed methods for identifying consumer experience is estimated.
Компьютерно-лингвистические методы и средства обнаружения потребительского опыта на веб-форумах
Computer and linguistic methods and means for identifying consumer experience on Web forums
Keywords: споживацький досвід; суб’єктивна інформація; веб-форум; інформаційний пошук; веб-спільноти; WWW; потребительский опыт; субъективная информация; веб-форум; информационный поиск; веб-сообщества; consumer experience; subjective information; Web forum; information retrieval; Web communities